EFEKTIVITAS SALEP KOMBINASI EKSTRAK DAUN BANGUN – BANGUN (Coleus amboinicus Lour.) DAN DAUN KELAPA SAWIT (Elaeis guineensis Jacq.) SEBAGAI OBAT LUKA SAYAT - Rika Puspita Sari (Jurnal Penelitian Farmasi & Herbal, 2020)
Bangun-bangun leaves and palm leaves contain various secondary metabolites such as tannins, alkaloids and flavonoids which can healing wound. The aim of this study was to determine the effect of ointment combination of ethanol extract of leaves of bangun- bangun (Coleus amboinicus Lour.) And ethanol extract of palm leaves (Elaeis guineensis Jacq.) In healing wound. The bangun- bangun leaves and the palm leaves are separated from the petiole and then dried in a drying cupboard so that it becomes a simplisia. Simplisia is extracted by maceration method then evaporated with a rotary evaporator and evaporated again on a water bath to produce a thick extract. Thick extracts from the leaves of bangun- bangun and palm leaves are then formulated into ointment preparations with varying concentrations. Each rabbit was shaved on its back then cleaned with 70% alcohol. Furthermore, rabbits were anesthetized using 0.5 ml Lidocain HCL as much as 0.5 ml subcutaneously. Next mark the part that will be injured with a diameter of 2 cm, by lifting the rabbit skin using tweezers and then made a wound using surgical scissors that have been sterilized first with 70% alcohol. Wound diameter measurements showed that all treatment groups from day 1 to day 23 experienced changes in wound diameter. The combination ointment of ethanol extract of leaves wake-up (EEDB) 10% and ethanol extract of palm oil leaves (EEDKS) 10% have a more effective effect in wound healing than single dose.